KONSEP MANUSIA DALAM AL-QUR’AN (Kajian Tafsir Tematik) - Muhamad Ali Mustofa Kamal (LP3M Universitas Sains Al Qur'an, 2016)
Humans are the most amazing creatures, the unique multi-dimensional beings, all-covering, very open, and has great potential. Its presence on earth has the vision and mission of God the Creator as an explanation of the Qur'an. Human resources play an important role in the prosperity of the earth. In this paper, discussion of interpretations of the human attempt to give enlightenment for every ones to its existence as a creature that can rank high on the side of his Lord on the contrary to be the lowest since the element of humanity is inherent in him. The element of faith and taqwa and his wisdom in instilling virtue is a pre-requisite that must be met to be a real man. Reviews on the history of man noted that humans have a superior characteristics in accordance with its function. The Qur'an specifically noted human functions that we should think together as teaching materials, devotional materials and ideas.